Linux custom wireless access point with authentication system / Abdul Hafiz Abd Wahid - Abd Wahid, Abdul Hafiz (2006)
The main goal of this thesis is to setup a custom wireless access point that can also perform a reliable authentication and encryption system. These are made possible by using the D-Link DWL-G520 108 Mbps PCI adapter which uses an Atheros ar5212 chipset. The authentication part uses the WPA-EAP authentication protocol which is implemented using FreeRadius server. This thesis involve configuring and testing the wireless access point making it a secure wireless device, and the effect of encryption on effective network bandwidth